Aanneming tot kind van God by Paulus in Romeine 8 teen die agtergrond van die Jerusalemse tempelkultus - Deel II - Van Aarde, A. (Verbum et ecclesia, 1998)
Paul’s notion of "adoption" in Romans 8 in the light of the Jerusalem temple cult In a previous article it was shown that the marriage arrangements advocated within the sphere of the Second Temple cult in Jerusalem provided the parameters for the use of the metaphor "Israel as family". When Paul explained who the people really were who constituted the true "Israel of God", he used the same metaphor as point of departure in spite of being influenced by the Greco-Roman thought and Hellenistic-Semitic wisdom tradition on the concept "divine sonship". This article aims to show how Paul, who personally did not know Jesus of Nazareth, continued to transmit the "heart" of Jesus’ message about children entering God’s kingdom. Paul achieved this by making use of the notion "adoption". The article describes the trajectory from Paul to Jesus to John the Baptist, the initiator of the idea of an inclusive and egalitarian community.